1998
DOI: 10.1046/j.1523-1755.1998.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of mast cells to the tubulointerstitial lesions in IgA nephritis

Abstract: Mast cells are one of the constitutive cells in the interstitium of IgA nephritis patients and affect renal function by contributing to the interstitial fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
86
2
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 27 publications
(20 reference statements)
4
86
2
1
Order By: Relevance
“…Intensity of specific mRNA bands was quantified by computer-assisted densitometry, normalized to the intensity of the 28S bands on the ethidium bromide-stained blots, and expressed as PAI-1/28S ratio (B, D, F, and H, mean Ϯ SD of three separate experiments). *P Ͻ 0.001 versus 0 h. extent of the infiltration was directly and significantly correlated with the degree of interstitial fibrosis (22).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Intensity of specific mRNA bands was quantified by computer-assisted densitometry, normalized to the intensity of the 28S bands on the ethidium bromide-stained blots, and expressed as PAI-1/28S ratio (B, D, F, and H, mean Ϯ SD of three separate experiments). *P Ͻ 0.001 versus 0 h. extent of the infiltration was directly and significantly correlated with the degree of interstitial fibrosis (22).…”
Section: Discussionmentioning
confidence: 85%
“…Mast cell infiltration has often been observed in chronic inflammation leading to tissue fibrosis in different organs, including lung, liver, skin, and kidney (21)(22)(23)(24). In particular, the presence of these immune cells was recently described within the interstitial space in IgAN by different authors (22). Interestingly, the E), and thrombin (G), harvested at the indicated time points and then total RNA was extracted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, sustained stimulation of AT2 receptors by the ARB-induced ANG II may upregulate the bradykinin production, 10,15,19,20 while ACE-I accumulates bradykinin by directly inhibiting its degradating enzyme. Furthermore, in renal disease, where chymase-containing mast cells prevail, 22 the non-ACE-dependent ANG II formation may be enhanced within the kidney, but not in systemic vascular beds; in contrast, ARB could disrupt the ANG II activity. Alternatively, the elevated urinary NO x may simply reflect a consequence of renal protection in the long-term treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells also produce a variety of cytokines that mediate delayed-type hypersensitivity (DTH) (9) and are key components of the pathogenesis of proliferative GN, injurious (e.g., TNF), and protective (e.g., IL-4) (20 -22). Experimental and human GN studies have demonstrated a strong correlation between the number of interstitial mast cells and severity of interstitial injury (19,(23)(24)(25). In inflammatory renal injury induced in rats by subtotal nephrectomy, a significant infiltration of mast cells in the tubulointerstitium was accompanied by increased IL-8, SCF, and TGF-␤ expression (26).…”
mentioning
confidence: 99%